Adat as a local ideology of indigenous people in political event - Sukri Tamma; Timo Markus Duile; Ramlah Daud (Department Anthropology, Faculty of Social and Political Sciences Hasanuddin University., 2020)
This article aims to show the phenomenon of Adat as an influential factor in Indonesia's regional election process after the New Order Era. The phenomenon seems to indicate a